How Well Do Children Understand the Vocabulary of Sleep? - Beris Ludwig; Simon S. Smith; Helen Heussler (SLACK Incorporated, 2019)
Background: Sleep surveys, such as the Pediatric Daytime Sleepiness Scale (PDSS), are used to determine a variety of concerns associated with sleep, including excessive daytime sleepiness (hypersomnolence), bedtime sleep behaviors, night awakenings, sleep duration, and sleep-disordered breathing. However, the literacy ability of the patient may not be adequate to ensure comprehension of questions and provision of accurate responses. Objective: To assess children's understanding of the sleep-associated vocabulary included in the PDSS. Methods: A cross-sectional, open-response survey was developed for use with students age 4 to 12 years. Prior to completing the instrument, each student was asked the meaning of six key sleep-related words used in the PDSS: drowsy, sleepy, alert, awakened, tired, and awake. The parents/caregivers were requested to record their child's definitions of these key words exactly as stated. Identification of words for "suitable" definitions was undertaken through consultation of three online dictionaries. This enabled the qualitative process associated with open-response surveys to be followed: identification of common themes, chunking of information, and criteria for coding responses. The final sample consisted of word definitions from 325 students (152 boys and 173 girls) from a school enrollment of 727 (45%). Key Results: A high percentage of children provided "suitable" responses for the words sleepy (84%) and tired (75%). The percentage of "suitable" responses for the words drowsy and awakened gradually increased across the age groups. The words alert and awake were challenging for the children to define, with the sleep-associated definition for alert only being provided by 31% of children overall and awake only being provided by 48% overall. In total, 57% of children were able to provide suitable definitions for at least four words. Conclusions: Our findings suggest that the results of many sleep surveys using these terms may not yield results that accurately reflect a child's actual state of daytime sleepiness and sleep/wake behaviors. Prior to administering a sleep survey, physicians need to clearly explain the meanings of sleep-associated words used in the survey and thus gain a more accurate reflection of a child's sleep and daytime behaviors.